The cost of waste of consumable materials in a surgical center - Liliana Cristina de Castro; Valeria Castilho (Universidade de São Paulo, 2013)
OBJECTIVES: to identify the types, quantities and cost of the consumable materials sent, used, returned unopened and wasted in surgical operations; to classify the incidences of waste as avoidable or unavoidable losses, and to calculate the rate of waste of the consumable materials in the peri-operative period in the Surgical Center of a São Paulo university hospital. METHOD: a descriptive-exploratory case study with a quantitative approach. The convenience sample corresponded to 105 types of consumable materials sent for the 275 operations observed between February and May 2011. RESULTS: the items wasted most were surgical sutures, surgical cotton sutures, and gauze compresses. The total cost of the waste was R$ 709.84. The mean percentage of waste in the sample was 9.34%, of which 1.23% was avoidable and 8.14% unavoidable. CONCLUSION: the study evidenced that the effective management of material resources reduces the costs of the processes, and reduces waste.